Reliability and associated risk factors for performance on the vestibular/ocular motor screening (VOMS) tool in healthy collegiate athletes - Kontos, A. P.; Sufrinko, A.; Elbin, R. J.; Puskar, A.; Collins, M. W. (The American Journal of Sports Medicine, 2016)
Background: The Vestibular/Ocular Motor Screening (VOMS) is a newly developed screening tool that evaluates vestibular and ocular motor symptom (eg, headache, dizziness, nausea, fogginess) provocation after a sport-related concussion. Baseline data on the VOMS are needed to extend the application of this measure to broad age groups and to document normal variations in performance. Purpose: The primary purpose of this study was to examine the internal consistency of the VOMS in a large sample of healthy, nonconcussed collegiate athletes. The secondary purpose was to investigate the effects of patient sex and history of motion sickness, migraines, and concussions on baseline VOMS scores. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 263 National Collegiate Athletic Association Division I athletes (mean ± SD age, 19.85 ± 1.35 years) completed self-reported demographic and medical history at preseason physical examinations and baseline screening. Internal consistency of the VOMS was assessed with Cronbach a. A series of univariate nonparametric tests (2 with odds ratios [ORs] and 95% CIs) were used to examine the associations among medical history risk factors and VOMS clinical cutoff scores (score of =2 for any individual VOMS symptom, near point of convergence [NPC] distance of =5 cm), with higher scores representing greater symptom provocation. Results: Internal consistency of the VOMS was high (Cronbach a = .97), and 89% of athletes scored below cutoff levels (ie, 11% false-positive rate). Female athletes (OR, 2.99 [95% CI, 1.34-6.70]; P = .006) and those with a personal history of motion sickness (OR, 7.73 [95% CI, 1.94-30.75]; P = .009) were more likely to have =1 VOMS scores above cutoff levels. No risk factors were associated with increased odds of an abnormal NPC distance. Conclusion: The VOMS possesses internal consistency and an acceptable false-positive rate among healthy Division I collegiate student-athletes. Female sex and a history of motion sickness were risk factors for VOMS scores above clinical cutoff levels among healthy collegiate student-athletes. Results support a comprehensive baseline evaluation approach that includes an assessment of premorbid vestibular and oculomotor symptoms.